2007
DOI: 10.1029/2006gl027372
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble‐mean dynamics of the ENSO recharge oscillator under state‐dependent stochastic forcing

Abstract: [1] In this paper, the conceptual recharge oscillator model for the El Niño-Southern Oscillation phenomenon (ENSO) is utilized to study the influence of fast variability such as that associated with westerly wind bursts (WWB) on dynamics of ENSO and predictability. The ENSO-WWB interaction is simply represented by stochastic forcing modulated by ENSO-related sea surface temperature (SST) anomalies. An analytical framework is developed to describe the ensemble-mean dynamics of ENSO under the stochastic forcing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
162
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(171 citation statements)
references
References 34 publications
6
162
3
Order By: Relevance
“…However, since version 3.5, CCSM represents ENSO as a series of events, owing to improved simulation of the meridional extent of the wind anomalies and their associated ocean response (Neale et al 2008). In the real world, warm events also appear to arise from a stable basic state excited by stochastic forcing (Penland and Sardeshmukh 1995;Thompson and Battisti 2001;Kessler 2002 Jin et al 2007); however, our choice of white Gaussian noise with a 1-month decorrelation time scale produces an adequate simulation of the CCSM4 ENSO, given the simplicity of the model. Therefore, nonlinear and seasonally dependent feedbacks excited with Gaussian white noise appear to be the most parsimonious model of CCSM4's La Niña.…”
Section: B Effect Of External Noisementioning
confidence: 99%
See 1 more Smart Citation
“…However, since version 3.5, CCSM represents ENSO as a series of events, owing to improved simulation of the meridional extent of the wind anomalies and their associated ocean response (Neale et al 2008). In the real world, warm events also appear to arise from a stable basic state excited by stochastic forcing (Penland and Sardeshmukh 1995;Thompson and Battisti 2001;Kessler 2002 Jin et al 2007); however, our choice of white Gaussian noise with a 1-month decorrelation time scale produces an adequate simulation of the CCSM4 ENSO, given the simplicity of the model. Therefore, nonlinear and seasonally dependent feedbacks excited with Gaussian white noise appear to be the most parsimonious model of CCSM4's La Niña.…”
Section: B Effect Of External Noisementioning
confidence: 99%
“…A1a,b, green line). These differences arise because the zonal current anomaly u 0 comprises a wind-driven component-a direct response to the wind anomalies-and a Kelvin wave componentassociated with the delayed thermocline response (Jin et al 2006). The Q 0 u variability correlated with SST anomalies contributes to the positive Bjerknes feedback (in the same way than Q 0 w ), while the variability in quadrature contributes to the delayed thermocline feedback.…”
Section: Composite Heat Budget Analysismentioning
confidence: 99%
“…Tsyrulnikov (2005) utilized this idea to characterize the combined effect of the sub-grid parameterization, the unrecognized physical processes, and the atmospheric noise by adopting the Markov chain models; Jin et al (2007) used state-dependent stochastic noise to represent combined model errors and study the predictability and dynamics of the ENSO recharge oscillator. Zheng and Zhu (2016) added random terms to the tendency of an ENSO model and explicitly defined them as model errors.…”
Section: Introductionmentioning
confidence: 99%
“…Palmer (2001) suggested that subgrid processes could be represented by simplified nonlinear stochastic-dynamic models as an alternative to the deterministic bulk-formula approach. Shutts (2005) and Shutts and Palmer (2007) showed that a cellular automaton scheme to introduce stochastic perturbations in the physical tendencies had a beneficial impact in a mediumrange global forecast model, while Jin et al (2007) employed a state-dependent stochastic multiplicative forcing to improve El Niño-Southern Oscillation (ENSO) simulations in a simplified model.…”
Section: Introductionmentioning
confidence: 99%